Organic–Inorganic Perovskite Memristors: Photoassisted Electroforming Method for Reliable Low‐Power Organic–Inorganic Perovskite Memristors (Adv. Funct. Mater. 17/2020). (27th April 2020) - Zhao, Xiaoning; Wang, Zhongqiang; Li, Wentong; Sun, Shaowu; Xu, Haiyang; Zhou, Peng; Xu, Jiaqi; Lin, Ya; Liu, Yichun
Abstract : In article number 1910151, Haiyang Xu, Peng Zhou, Yichun Liu, and co‐workers propose a photo‐assisted electroforming strategy in organic–inorganic hybrid perovskite memristors. The mild method can effectively suppress the undesirable current overshoot and enable reliable low power CH3 NH3 PbI3 ‐based memristors. The proposed strategy provides a simple and effective way to optimize the performance of memristors based on light‐sensitive materials.